Sarcoidosis-associated pulmonary fibrosis: joining the dots - Bandyopadhyay, Debabrata; Mirsaeidi, Mehdi S. (European respiratory review, 2023)
Sarcoidosis is a multisystem granulomatous disorder of unknown aetiology. A minority of patients with sarcoidosis develop sarcoidosis-associated pulmonary fibrosis (SAPF), which may become progressive. Genetic profiles differ between patients with progressive and self-limiting disease. The mechanisms of fibrosis in SAPF are not fully understood, but SAPF is likely a distinct clinicopathological entity, rather than a continuum of acute inflammatory sarcoidosis. Risk factors for the development of SAPF have been identified; however, at present, it is not possible to make a robust prediction of risk for an individual patient. The bulk of fibrotic abnormalities in SAPF are located in the upper and middle zones of the lungs. A greater extent of SAPF on imaging is associated with a worse prognosis. Patients with SAPF are typically treated with corticosteroids, second-line agents such as methotrexate or azathioprine, or third-line agents such as tumour necrosis factor inhibitors. The antifibrotic drug nintedanib is an approved treatment for slowing the decline in lung function in patients with progressive fibrosing interstitial lung diseases, but more evidence is needed to assess its efficacy in SAPF. The management of patients with SAPF should include the identification and treatment of complications such as bronchiectasis and pulmonary hypertension. Further research is needed into the mechanisms underlying SAPF and biomarkers that predict its clinical course.